2010
DOI: 10.1590/s0104-56872010000300017
|View full text |Cite
|
Sign up to set email alerts
|

Teste GIN (Gaps-in-Noise) em ouvintes normais com e sem zumbido

Abstract: Background: the Gaps-in-Noise (GIN) test assesses the auditory temporal resolution skill. Studies have described the GIN test an instrument of easy application and with good sensitivity and specificity. Aim: to compare the results of the GIN test in normal listeners with and without tinnitus and to correlate the obtained results with pure tone thresholds and age. Method: hearing tests were performed in 44 subjects (hearing threshold up to 25 dB HL in the frequencies of 0.25 to 8 kHz). Two groups were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
2
8
0
3
Order By: Relevance
“…The results obtained in the Control Group and Study Group approached those found in the literature [10][11][12][13][14][15] . It can be considered that the samples of the present study are within the normal ranges.…”
Section: Discussionsupporting
confidence: 84%
“…The results obtained in the Control Group and Study Group approached those found in the literature [10][11][12][13][14][15] . It can be considered that the samples of the present study are within the normal ranges.…”
Section: Discussionsupporting
confidence: 84%
“…They postulated that the reason for poor gap detection could be that ongoing tinnitus masks the gap and results in impaired gap detection. Sanchez et al 13 used the Gap in noise test on normal hearing listeners to evaluate the auditory temporal resolution ability of 18 individuals with tinnitus and 23 individuals without tinnitus. They reported that individuals without tinnitus detected shorter gaps than individuals with tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez et al 13 compared the results of the gaps in noise test in normal hearing subjects with and without tinnitus. Results showed that individuals with tinnitus detected silence gaps with larger time of interval than the non-tinnitus individuals; i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The stimuli were presented at 40 dB HL from the mean tonal thresholds at 500 Hz, 1000, 2000, 3000 and 4000 Hz, for each ear. The presentation was in the binaural condition, of a gap inserted in pairs of pure tones in the frequencies of 500, 1000, 2000 and 4000 Hz, with intervals between the two pure tones that ranged from 0 to 40 ms (RGDT) 15 . The subject was instructed to indicate with his/her fingers the amount of one or two, referring to the number of stimuli detected.…”
Section: Methodsmentioning
confidence: 99%
“…The GIN test was also performed at 40 dB HL from the mean tonal thresholds of 500 Hz to 4000 Hz. Each of the test strips consists of the presentation of ten gaps (2,3,4,5,6,8,10,12,15 and 20 ms) with different durations, being presented six times each, for a total of 60 gaps. The subjects were told they would hear noises and, within these noises, there would be silence intervals (gaps), being up to 3 intervals of silence at the same noise and also noise without interval of silence.…”
Section: Methodsmentioning
confidence: 99%